Highly reliable DHR-based polar compilation code communication method - Zheng, Yulu; Gu, Tiansheng; Liu, Shangdong; Shao, Sisi; Yang, Qian; Du, Hongyu; Shi, Yuchen; Nie, Yijun; Ji, Zongkai; Ji, Yimu (Computer networks (Amsterdam, Netherlands : 1999), 2024)
The advent of fifth-generation mobile communication technology, 5G, has raised the bar for data transmission rates, information security, and reliability. Polar codes, the channel coding scheme in the 5G communication standard, encounter issues of singularity, limitations, and passivity in the face of unknown attacks. Therefore, this study introduces a highly reliable DHR-based polar coding communication approach. Drawing parallels between cyber attacks and channel noise, the method incorporates reconfigurable executors, decoding decisions, strategy scheduling, and other mechanisms to enable active defense. The True Relatively Axiom (TRA) is employed to theoretically validate the method’s heterogeneity, redundancy, and dynamics. Comparative simulation experiments with traditional polar decoding algorithms, such as SCL, SC, BP, SCAN, and SSC decoding algorithms, demonstrate that the proposed method not only improves secure transmission efficiency but also guarantees secure and reliable transmission across various attack scenarios. Our code is available at https://github.com/yuluzi/my-code.git.